Early Effects of Passive Leg-Raising Test, Fluid Challenge, and Norepinephrine on Cerebral Autoregulation and Oxygenation in COVID-19 Critically Ill Patients - Robba, Chiara; Messina, Antonio; Battaglini, Denise; Ball, Lorenzo; Brunetti, Iole; Bassetti, Matteo; Giacobbe, Daniele R.; Vena, Antonio; Patroniti, Nicolo'; Cecconi, Maurizio; Matta, Basil F.; Liu, Xiuyun; et al. (Frontiers in Neurology, 2021)
Purpose: COVID-19 patients are at high risk for neurological complications consequent to several factors including persistent hypotension. There is a paucity of data on the effects of therapeutic interventions designed to optimize systemic hemodynamics on cerebral autoregulation (CA) in this group of patients. Methods: Single center, observational prospective study conducted at San Martino Policlinico Hospital, Genoa, Italy from 1st October to 15th December 2020. Mechanically ventilated severe COVID-19 patients, who had at least one episode of hypotension and received a passive leg raising (PLR) test were included. They were then treated with fluid challenge (FC) and/or norepinephrine (NE), according to patients’ clinical conditions, at different moments. The primary outcome was to assess the early effects of PLR test and of FC and NE (when clinically indicated to maintain adequate mean arterial pressure (MAP)) on CA (CA index) measured by Transcranial Doppler (TCD)]. Secondary outcomes were to evaluate the effects of PLR test, FC and NE on systemic hemodynamic variables, cerebral oxygenation (rSO2) and noninvasive intracranial pressure (nICP). Results: Twenty-three patients were included and underwent PLR test. Of these, 22 patients received FC and 14 were treated with NE. The median age was 62 years [Interquartile range, IQR=57-68.5], and 78% of patients were male. PLR test led to a low CA index [58 %(44-76.3)]. FC and NE administration resulted in a CA index of 90.8 (74.2-100) and 100 (100-100)%, respectively. After PLR test, both nICP based on pulsatility index and on flow velocity diastolic formula were increased [18.6 (17.7-19.6) vs 19.3 (18.2-19.8) mmHg, p=0.009,and 12.9(8.5-18) vs 15(10.5-19.7) mmHg, p=0.001,respectively]. PLR test, FC and NE resulted in a significant increase of MAP and rSO2. Conclusions: In mechanically ventilated severe COVID-19 patients, PLR test adversely affects CA. An individualized strategy aimed to assess both the hemodynamic and cerebral needs is warranted in patients at high risk of neurological complications.